(untitled) (Research, Society and Development, 2020)
The application of natural substances with bactericidal action is the target of research aimed at a more sustainable production, implying in various sources of substances for new therapeutic formulations. This study presents the chemical characterization, toxicity and antimicrobial activity of essential oil (EO) of Bixa orellana Labill leaves. EO was extracted by hydrodistillation at 100°C for 3h. Physicochemical parameters were determined and chemical characterization used Gas chromatography coupled with Mass Spectrometry (GC/MS). The toxicity assay was performed through the bioassay with Artemia salina Leach. The methods of Disc Diffusion and Dilution in Broth in front of the bacteria Escherichia coli and Staphylococcus aureus were used to evaluate the antimicrobial activity. LC50 in the toxicity assay was verified in 355 mg L-1 and was classified as nontoxic. The OE presented antimicrobial activity against the microorganisms tested and totaled 320 mg EAT g-1 of total phenolics. The results obtained highlight the importance of pointing out this product as a therapeutic alternative, encouraging its application potential.